Inflectional Process in the Spanish Lyrics of “On My Way”: A Morphological Study - Valencia Friska Suarliem; Ni Made Diana Erfiani; Yohanes Octovianus L. Awololon; I Nengah Laba (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The aim of the study was to analyze the inflectional process towards the words in “On My Way” song’s lyric by Alan Walker feat. Sabrina Carpenter and Farukko. The study employed the descriptive-qualitative method to understand the inflectional process without numerical data. The data, which sourced from the lyrics of “On My Way” song, were collected through documentation, content-analysis, and interview techniques. Inflectional morphology was used to analyze the data through data condensation, data display, and conclusion drawing and verifying. The result showed that 16 inflected words were found, which the words underwent conjugation were found the most, followed by gender and plurality.